ANALISIS TINGKAT KECEMASAN SISWA DALAM PEMBELAJARAN MATEMATIKA BERDASARKAN HASIL SURVEI PADA SISWA SMP NEGERI 12 KOTA JAMBI - Indah Nuriyana; Adroki Hidyan; Sophi Sabrina; Adrian Maulana Sidiq; Nofverma; Husni Sabil (STKIP Subang, 2026)
This study aims to determine and analyze the level of student anxiety in mathematics learning at SMP Negeri 12 Kota Jambi. Mathematics anxiety is an affective barrier that often interferes with students' cognitive processing during the learning process. This research employs a quantitative descriptive survey method. The research respondents consisted of 21 junior high school students selected using purposive sampling. Data were collected using a mathematics anxiety questionnaire instrument consisting of 25 statement items measured on a Likert scale. The results showed that the total actual score obtained was 1,623 out of a maximum ideal score of 2,625. Based on the percentage index calculation, a value of 61.83% was obtained. Therefore, it can be concluded that the level of anxiety in learning mathematics among students of SMP Negeri 12 Kota Jambi is in the